KONVENSI KETATANEGARAAN SEBAGAI BATU UJI DALAM PENGUJIAN UNDANG-UNDANG DI MAHKAMAH KONSTITUSI - Weldy Agiwinata (Universitas Airlangga, 2014)
This research attempts to analyze in normative manner the use of constitutional convention as source of laws and cause of action for Constitutional Court (Mahkamah Konstitusi) in constitutional review and to explain further the meaning of constitutional convention as unwritten law. This research indicates that: constitutional convention cannot be included into legal regulation hierarchy. Refers to the meaning and concept of convention as unwritten law cannot be included because it will violate the essence of constitutional convention as unwritten law; The role of constitutional law is to cover the weaknesses of constitutional regulations can be used as a companion to written constitution serves as reference for The Constitutional Court, so that the existing and respected constitutional values and practices need to be considered. It also functions to preserve values which are considered as sacred or it is considered impossible to amend the constitution quickly because of constitutional issues.Keywords: constitutional court, constitutional convention, unwritten law